2015
DOI: 10.1111/sms.12465
|View full text |Cite
|
Sign up to set email alerts
|

Alpine Skiing With total knee ArthroPlasty (ASWAP): clinical and radiographic outcomes

Abstract: The aim of the study was to assess the effect of a recreational alpine skiing intervention on implant-related factors, such as loosening and wear, in patients with total knee arthoplasty (TKA). A group of 16 TKA patients were examined 2.3 ± 0.1 years after skiing about 80 days over three seasons inclusive of a ski intervention of 2-3 times per week (25.5 days) over a 12-week period. Mean follow-up period was 5.1 ± 1 years after surgery. All patients had excellent clinical and radiological outcomes. The average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
1
13
0
1
Order By: Relevance
“…Hence, as muscle fatigue is known to increase injury risk [10], there might be no additional high risk for injuries for TKA patients with pre-existing skiing experience. This lends support to a prior study on the clinical and radiographic outcome of alpine skiers after 80 days of skiing within three years, where the authors did not observe any significant injury [46]. Furthermore, the Knee Society Score, measured before and 14 days after the investigation, remained stable.…”
Section: Discussionsupporting
confidence: 85%
“…Hence, as muscle fatigue is known to increase injury risk [10], there might be no additional high risk for injuries for TKA patients with pre-existing skiing experience. This lends support to a prior study on the clinical and radiographic outcome of alpine skiers after 80 days of skiing within three years, where the authors did not observe any significant injury [46]. Furthermore, the Knee Society Score, measured before and 14 days after the investigation, remained stable.…”
Section: Discussionsupporting
confidence: 85%
“…The following exclusion criteria were used: severe arthritic involvement of other joints and systemic pathologies. Indication for TKA was primary degenerative osteoarthritis in all cases (Hofstaedter et al., ). In the present substudy, only participants with a unilateral TKA were included.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 However, few studies have investigated the effects of higher-impact activities like skiing on the longevity of an artificial knee. [8][9][10] Although there are studies in the literature regarding the physiologic impact to implants from sports participation after arthroplasty, 11,12 surgeons' perspectives on return to specific sports are less well known. McGrory and colleagues 3 found that orthopedic surgeons, fellows and residents would recommend (based on 75% consensus) lowimpact sports such as swimming, golfing, bowling and cycling after knee replacement, but not higher-impact sports such as running, racquetball, basketball or football because of the perceived increased risk to the artificial joint.…”
mentioning
confidence: 99%